Efektivitas Pelatihan Psychological First Aid (PFA) Perempuan Korban Pelecehan Seksual Terhadap Empati Mahasiswa Psikologi Unibi - Dyah Rachman Kuswartanti; Cahayaning Widhyastuti; Nida Muthi Annisa (Guidena)
Sexual harassment against women is increasing. Data from the National Commission of Violence Against Women (Komnas Perempuan) shows that the number of sexual violence increased by 6% in 2019. And the most reported was Cyber Gender-Based Violence (KBGS). Most women feel ashamed and find it difficult to report sexual harassment because there are still many views Indonesian people who view this as taboo. Victims of Sexual harassment need first aid to cope with their experience as a victim that could trigger a traumatic experience. UNIBI psychology students are expected to have good empathy in helping people because they are considered to be more knowledge and skill. This research examined the empathy of UNIBI psychology students when they know or see sexual harassment before (pre-test) and after (post-test) doing Psychological First Aid (PFA). In this research, researchers used the one-group pre-test post-test design experimental method to see differences in empathy before and after treatment. The measurement of empathy in this study used the Interpersonal Reactivity Index (IRI) empathy scale with 18 respondents. Analysis of the research data using paired samples t-test analysis with a significance result of 0.325; p > 0.05. these results indicate that giving Psychological First Aid (PFA) to female victims of sexual harassment is not effective in increasing the empathy of UNIBI psychology students.